ANALISIS DAMPAK PENGGUNAAN MEDIA SOSIAL TERHADAP KARAKTER TOLERANSI SISWA SEKOLAH DASAR - Dia, Riana; Kuntarto , Eko; Muhammadin Alfath, Ayatullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of information technology in the digital era has led to increased social media use among elementary school students. Social media platforms such as TikTok and YouTube provide a variety of content that can influence student behavior and character development, including tolerance. This study aims to analyze the impact of social media use on the tolerance character of elementary school students. This research used a qualitative approach with a descriptive approach. The study was conducted at SDN 10/IV, Jambi City, with fourth-grade students as subjects, along with teachers and parents as supporting informants. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. Data validity was tested through triangulation of sources and techniques. The results indicate that social media use has both positive and negative impacts on students' tolerance character. Positive impacts are seen in increased creativity, courage in expressing opinions, and broadening students' horizons. However, negative impacts were also found, such as the use of impolite language, a tendency to ridicule peers, and a reduced appreciation for differences. Therefore, schools, teachers, and parents need to play an active role in guiding the wise use of social media and instilling values ​​of tolerance through learning activities and practices within the school environment.